Respiratory health effects of e-cigarette substitution for tobacco cigarettes: a systematic review - Maria Ahmed Qureshi; Robin W. M. Vernooij; Giusy Rita Maria La Rosa; Riccardo Polosa; Renee O'Leary (BMC, 2023)
Abstract Background E-cigarettes (electronic nicotine delivery system, ENDS) have been presented as a harm reduction strategy for people who smoke tobacco cigarettes but who cannot achieve abstinence, or for those who wish to continue to enjoy nicotine and the habit of smoking. What are the health effects of the substitution of ENDS for tobacco cigarettes? This systematic review evaluates the evidence of human clinical tests on the respiratory effects of ENDS use in participants who smoke tobacco cigarettes. Methods A registered and published protocol was developed conforming to PRISMA 2020 and AMSTAR2 standards. The literature search was conducted in PubMed, Scopus, and the CENTRAL Cochrane Library and updated to May 2022. Three supplementary searches and a grey literature search were performed. Studies were evaluated with the JBI quality tools and the Oxford Catalogue of Bias. Due to the heterogeneity (diversity) of the studies, a narrative data synthesis was performed on the test findings plus three sub-group analyses. Results The review consists of sixteen studies and twenty publications. Spirometry tests comprised the majority of the data. In total, 66 respiratory test measurements were reported, out of which 43 (65%) were not significant. Statistically significant findings were mixed, with 9 tests showing improvements and 14 measuring declines, none of which was clinically relevant. Ten studies were rated at a high risk of bias, and six had some concerns primarily due to inadequate research designs and the conduct of the studies. Reporting bias was documented in thirteen studies. Conclusions Most of the studies showed no difference in respiratory parameters. This indicates that ENDS substitution for smoking likely does not result in additional harm to respiratory health. Due to the low quality of the studies, confidence in the conclusions is rated as low. Robust studies with a longer duration and sufficient power are required to validate any potential benefits or possible harms of ENDS substitution. Registration PROSPERO #CRD42021239094, International Registered Report Identifier (IRRID): DERR1-10.2196/29084.